Sex differences in the hypothalamic–pituitary–adrenal axis’ response to stress: an important role for gonadal hormones - Heck, Ashley L. (Neuropsychopharmacology, 2018)
The hypothalamic–pituitary–adrenal (HPA) axis, a neuroendocrine network that controls hormonal responses to internal and external challenges in an organism’s environment, exhibits strikingly sex-biased activity. In adult female rodents, acute HPA function following a stressor is markedly greater than it is in males, and this difference has largely been attributed to modulation by the gonadal hormones testosterone and estradiol. These gonadal hormones are produced by the hypothalamic–pituitary–gonadal (HPG) axis and have been shown to determine sex differences in adult HPA function after acute stress via their activational and organizational effects. Although these actions of gonadal hormones are well supported, the possibility that sex chromosomes similarly influence HPA activity is unexplored. Moreover, questions remain regarding sex differences in the activity of the HPA axis following chronic stress and the underlying contributions of gonadal hormones and sex chromosomes. The present review examines what is currently known about sex differences in the neuroendocrine response to stress, as well as outstanding questions regarding this sex bias. Although it primarily focuses on the rodent literature, a brief discussion of sex differences in the human HPA axis is also included.